Relatório de Estágio Profissional "Ensinar onde Aprendi" - Ana Rita da Costa Borges (2017)
As a way to close a chapter of my life, to fulfill one of my dreams, in order to finalize one of my greatest goals: the completion of the 2nd Cycle in Teaching of Physical Education in Primary and Secondary Education, in the Faculty of Sports of the University of Porto, I hereby accompany myself with the current document regarding my Professional Internship's Report. The Internship's Report is presented as a personalized document, where my experience as a teacher is portrayed. It also represents a decisive stage in my training, where subjects which were learned are highlighted. Regarding my Professional Internship, it was developed in Ermesinde Secondary School, under supervision of a supervising teacher and a cooperating teacher, as well as with the participation and cooperation of two nucleus colleagues and yet another internship nucleus, inserted in the same school. Regarding the document's structure, it is divided in four areas: Organization and Management of Teaching and Learning, School Participation, Relations with the Community and Professional Development. Besides these large fields, the personal, operational and institutional are also contextualized. Furthermore, research on the "Ideal Teacher vs Real Teacher", performed throughout the school year, is also included in the document. Willing to learn and afraid to make mistakes, attentive and curious, nervous and anxious, I began and finalized my professional internship, formalized in the current document.